A study on students perception towards the need of implementation of Automated Enforcement System (AES) at the intersection of traffic light in front of Universiti Malaysia Sabah (UMS) / Nurfatin Amalina Abdul Rahman and Nor Mazura Hassan - Abdul Rahman, Nurfatin Amalina; Hassan, Nor Mazura (2015)
The researchers had seen the problem of high rates of accidents and road rules violations at the intersection of traffic light in front of Universiti Malaysia Sabah (UMS). The study examines the correlation between perception of students and the factors that leads towards the needs of implementation of Automated Enforcement System (AES) at the area of study. A set of 199 questionnaires had been distributed to students of Year 2, Social Science Courses of Universiti Malaysia Sabah (UMS). The study reveals that there is high correlation between perception of students and the factors that leads towards the needs of implementation of Automated Enforcement System (AES) at the intersection of traffic light in front of Universiti Malaysia Sabah (UMS).